Glass glaze for high-gradient ZnO resistor disc as well as preparation method and application of glass glaze

By preparing lead-free low-temperature glass glaze with controllable expansion coefficient, the insulation problem of high-gradient ZnO resistor sheet under high voltage conditions is solved, and the crack-free and insulation effect of the glaze surface is improved.

CN119504286APending Publication Date: 2025-02-25XIAN XD ARRESTER CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411651770.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The residual voltage of the high-gradient ZnO resistor plate per unit height resistance plate is significantly increased under high voltage conditions, resulting in strict requirements on the side insulation of the varistor. External insulation of conventional epoxy resins is difficult to meet, and side flashover problems are prone to occur.

Method used

Using lead-free low-temperature glass glaze with a controllable expansion coefficient, glass glaze suitable for high-gradient ZnO resistive sheets is prepared by mixing solid raw materials with sodium polyacrylate and polyvinyl alcohol ball mill, spray granulation and sintering, combined with the melting treatment and pulverization of low-temperature glass powder.

Benefits of technology

This method matches the expansion coefficient of the glass glaze with the ZnO resistor sheet, avoids glaze cracks, and meets the insulation requirements of the high-gradient ZnO resistor sheet, and improves the capacity resistance passing rate of the resistor sheet and the high current impact resistance passing rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005141126670000011
    Figure HDA0005141126670000011
  • Figure HDA0005141126670000012
    Figure HDA0005141126670000012
  • Figure HDA0005141126670000021
    Figure HDA0005141126670000021
Patent Text Reader

Abstract

The invention provides glass glaze for a high-gradient ZnO resistor disc as well as a preparation method and application of the glass glaze, and the preparation method comprises the following steps: mixing a spherical spodumene expansion coefficient adjusting material, low-temperature glass powder, polyvinylpyrrolidone and water to obtain slurry; the mass ratio of the spherical spodumene expansion coefficient adjusting material to the low-temperature glass powder is 1: (5-20); and coating the surface of the high-gradient ZnO resistor disc with the slurry, and vitrifying to obtain the glass glaze for the high-gradient ZnO resistor disc. The lead-free low-temperature gradient glass glaze is matched with the ZnO resistor disc, the glaze surface of the resistor disc is free of cracks before and after action, the insulation requirement of the high-gradient ZnO resistor disc can be met, and the capacity tolerance passing rate and the large-current impact tolerance passing rate of the resistor disc are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic components, and in particular relates to a glass glaze for a high-gradient ZnO resistor sheet, and a preparation method and application thereof. Background Art

[0002] ZnO varistors are made of ZnO as the main raw material, with a small amount of Bi2O3, MnO2, Sb2O3, Co2O3, SiO2 and Cr2O3 added, and are prepared by ceramic sintering technology. Due to its excellent nonlinear volt-ampere characteristics and large current capacity, ZnO varistors have been widely used as the core components of power system lightning arresters in power system lightning protection and power equipment protection. In recent years, the relevant research on high voltage gradient zinc oxide varistors has become one of the research hotspots in the field of zinc oxide lightning arresters. However, the study found that after the voltage gradient of the zinc oxide varistor valve plate is increased, the residual pressure of the unit height resistor under the 8 / 20μs waveform lightning impulse current and the 4 / 10μs waveform large impulse current increases significantly, which puts more stringent requirements on the side insulation of the varistor.

[0003] At present, high-gradient ZnO resistors require high-strength external insulation due to their high energy, and conventional epoxy resins are difficult to meet the requirements, and side flashover problems are prone to occur. Glass glaze has higher heat resistance and is more reliable. The commonly used lead-containing glass glaze has a low processing temperature and is not prone to cracks, but this material is not environmentally friendly. The main problem with lead-free glass glaze is that its expansion coefficient does not match that of the resistor body, and the surface of the glass glaze is prone to cracks after heat treatment. Summary of the invention

[0004] The object of the present invention is to provide a glass glaze for a high-gradient ZnO resistor, a preparation method and an application thereof. The expansion coefficient of the glass glaze in the present invention is controllable and adjustable, which not only matches the ZnO resistor, but also leaves no cracks on the glaze surface of the resistor before and after operation, and can also meet the insulation requirements of the high-gradient ZnO resistor.

[0005] The present invention provides a method for preparing a glass glaze for a high-gradient ZnO resistor, comprising the following steps:

[0006] A) solid raw material is mixed with sodium polyacrylate and polyvinyl alcohol by ball milling, and the obtained mixed material is spray granulated and sintered in sequence to obtain spherical spodumene expansion coefficient adjusting material;

[0007] The solid raw material comprises, by mass fraction, 25-35% of aluminum oxide, 45-55% of silicon dioxide and 10-20% of lithium carbonate;

[0008] The sintering temperature is 950-1100°C, the sintering holding time is 2-4 hours, and the sintering heating rate is 2-5°C min;

[0009] B) by mass fraction, 30-50% ZnO, 5-15% Bi2O3, 10-20% Al2O3, 5-15% B2O3 and 20-40% SiO2 are ball-milled and mixed, and the obtained mixture is melt-treated and pulverized in sequence to obtain a low-temperature glass powder;

[0010] The melt processing is carried out according to the following steps:

[0011] Preheating stage: heating from room temperature to temperature T1, keeping at T1 for 1 to 2 hours, 450℃≤T1≤500℃;

[0012] Heating stage: heating to temperature T2, keeping at T2 for 3 to 5 hours, 500<T2≤1000℃, heating rate is 2~5℃ / min,

[0013] Melting stage: heating to temperature T3, keeping at T3 for 2 to 4 hours, 1000℃<T3≤1300℃;

[0014] Cooling stage: quickly pour the molten glass into a water tank at 20-25°C to obtain a glass frit;

[0015] C) mixing the spherical spodumene expansion coefficient adjusting material, low-temperature glass powder, polyvinyl pyrrolidone and water to obtain a slurry;

[0016] The mass ratio of the spherical spodumene expansion coefficient adjusting material to the low-temperature glass powder is 1:(5-20);

[0017] D) coating the slurry on the surface of a high gradient ZnO resistor and then vitrifying the slurry to obtain a glass glaze for a high gradient ZnO resistor.

[0018] Preferably, the mass of the sodium polyacrylate is 0.2-2% of the mass of the solid raw material;

[0019] The mass of the polyvinyl alcohol is 2-5% of the mass of the solid raw material.

[0020] Preferably, the ball milling mixing time in step A) is 60 to 120 minutes; and the air pressure of the spray granulation in step A) is 1 to 2 bar.

[0021] Preferably, the ball milling mixing time in step B) is 4 to 6 hours, and the rotation speed of the ball milling mixing is 150 to 300 rpm.

[0022] Preferably, in the slurry in step C), the total mass fraction of the spherical spodumene expansion coefficient adjusting material and the low-temperature glass powder is 15-38%, the mass fraction of polyvinyl pyrrolidone is 2-5%, and the mass fraction of water is 60-80%.

[0023] Preferably, in the step D), the high gradient ZnO resistor is preheated at 140-160° C. for 3-5 hours and then coated with the slurry.

[0024] Preferably, the slurry is sprayed on the surface of the high gradient ZnO resistor, the pressure of the spray gun is 0.1-0.3 MPa, and the spraying amount of the slurry is 0.05-0.2 g / cm 3 .

[0025] Preferably, the temperature of the vitrification is 450-550° C., the heat preservation time of the vitrification is 1-3 hours, and the heating rate of the vitrification is 1-3° C. / min.

[0026] The invention provides a glass glaze for a high-gradient ZnO resistor sheet, which is prepared according to the preparation method described above.

[0027] The present invention provides the use of the glass glaze for high-gradient ZnO resistor as described above in the insulating layer of the high-gradient ZnO resistor.

[0028] The invention provides a method for preparing glass glaze for high-gradient ZnO resistor sheets, comprising the following steps: A) mixing solid raw materials with sodium polyacrylate and polyvinyl alcohol by ball milling, spray granulating and sintering the obtained mixture in sequence to obtain a spherical spodumene expansion coefficient regulating material; the solid raw materials include 25-35% of aluminum oxide, 45-55% of silicon dioxide and 15-25% of lithium carbonate by mass fraction; the sintering temperature is 950-1100° C., the sintering heat preservation time is 2-4 hours, and the sintering heating rate is 2-5° C. min; B) mixing 30-50% of ZnO, 5-15% of Bi2O3, 10-20% of Al2O3, 5-15% of B2O3 and 20-40% of SiO2 by ball milling, melting and crushing the obtained mixture in sequence to obtain a low-temperature glass powder; the melting The melting treatment is carried out according to the following steps: preheating stage: heating from room temperature to temperature T1, keeping temperature at T1 for 1 to 2 hours, 450°C≤T1≤500°C; heating stage: heating to temperature T2, keeping temperature at T2 for 3 to 5 hours, 500<T2≤1000°C, and heating rate of 2 to 5°C / min; melting stage: heating to temperature T3, keeping temperature at T3 for 2 to 4 hours, 1000°C<T3≤1300°C; cooling stage: quickly pouring the molten glass into a water tank at 20 to 25°C to obtain a glass frit; C) mixing the spherical spodumene expansion coefficient adjusting material, low-temperature glass powder, polyvinyl pyrrolidone and water to obtain a slurry; the mass ratio of the spherical spodumene expansion coefficient adjusting material to the low-temperature glass powder is 1:(5 to 20); D) coating the slurry on the surface of the high-gradient ZnO resistor and vitrifying it to obtain a glass glaze for the high-gradient ZnO resistor. The lead-free low-temperature gradient glass glaze in the present invention not only matches the ZnO resistor, and the resistor has no cracks on the glaze before and after the action, but also meets the insulation requirements of the high-gradient ZnO resistor, further improving the resistance capacity tolerance pass rate and large current impact tolerance pass rate of the resistor. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0030] Figure 1 This is a microscope picture of the glass glaze in Comparative Example 1 of the present invention;

[0031] Figure 2 This is a microscope picture of the glass glaze in Comparative Example 2 of the present invention;

[0032] Figure 3This is a microscope picture of the glass glaze in Comparative Example 3 of the present invention;

[0033] Figure 4 This is a microscope picture of the glass glaze in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The present invention provides a method for preparing a glass glaze for a high-gradient ZnO resistor, comprising the following steps:

[0035] A) solid raw material is mixed with sodium polyacrylate and polyvinyl alcohol by ball milling, and the obtained mixed material is spray granulated and sintered in sequence to obtain spherical spodumene expansion coefficient adjusting material;

[0036] The solid raw material comprises, by mass fraction, 25-35% of aluminum oxide, 45-55% of silicon dioxide and 10-20% of lithium carbonate;

[0037] The sintering temperature is 950-1100°C, the sintering holding time is 2-4 hours, and the sintering heating rate is 2-5°C min;

[0038] B) by mass fraction, 30-50% ZnO, 5-15% Bi2O3, 10-20% Al2O3, 5-15% B2O3 and 20-40% SiO2 are ball-milled and mixed, and the obtained mixture is melt-treated and pulverized in sequence to obtain a low-temperature glass powder;

[0039] The melt processing is carried out according to the following steps:

[0040] Preheating stage: heating from room temperature to temperature T1, keeping at T1 for 1 to 2 hours, 450℃≤T1≤500℃;

[0041] Heating stage: heating to temperature T2, keeping at T2 for 3 to 5 hours, 500<T2≤1000℃, heating rate is 2~5℃ / min,

[0042] Melting stage: heating to temperature T3, keeping at T3 for 2 to 4 hours, 1000℃<T3≤1300℃;

[0043] Cooling stage: quickly pour the molten glass into a water tank at 20-25°C to obtain a glass frit;

[0044] C) mixing the spherical spodumene expansion coefficient adjusting material, low-temperature glass powder, polyvinyl pyrrolidone and water to obtain a slurry;

[0045] The mass ratio of the spherical spodumene expansion coefficient adjusting material to the low-temperature glass powder is 1:(5-20);

[0046] D) coating the slurry on the surface of a high gradient ZnO resistor and then vitrifying the slurry to obtain a glass glaze for a high gradient ZnO resistor.

[0047] Preparation of Spherical Spodumene Expansion Coefficient Adjusting Material

[0048] In the solid raw material, the mass fraction of the aluminum oxide is preferably 25-35%, more preferably 30%, such as 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, preferably a range value with any of the above values ​​as the upper or lower limit; the mass fraction of the silicon dioxide is preferably 45-55%, more preferably 50%, such as 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, preferably a range value with any of the above values ​​as the upper or lower limit; the mass fraction of the lithium carbonate is preferably 10-20%, more preferably 15-20%, such as 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0049] In the present invention, the mass of the sodium polyacrylate is 0.2-2% of the mass of the solid raw material, and more preferably 0.5-1.5%, such as 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0050] In the present invention, the mass of the polyvinyl alcohol is 2-5% of the mass of the solid raw material, preferably 3-4%, such as 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, preferably a range value with any of the above values ​​as the upper or lower limit.

[0051] In the present invention, the ball milling time is preferably 60 to 120 minutes, more preferably 90 minutes; the air pressure of the spray granulation is preferably 1 to 2 bar.

[0052] In the present invention, the sintering is preferably carried out in a muffle furnace, the sintering temperature is preferably 950-1100°C, more preferably 1000-1050°C, the sintering holding time is preferably 2-4 hours, more preferably 2-3 hours; the sintering heating rate is preferably 2-5°C / min, more preferably 3-4°C / min.

[0053] Preparation of low temperature glass powder

[0054] In the present invention, the low-temperature glass powder comprises the following raw materials in mass fractions:

[0055] ZnO: 30%~50%

[0056] Bi2O3: 5%~15%

[0057] Al2O3: 10%~20%

[0058] B2O3: 5%~15%

[0059] SiO2: 20%~40%

[0060] In the present invention, the mass fraction of ZnO is preferably 30-50%, more preferably 35-45%, such as 30%, 35%, 40%, 45%, 50%, preferably a range value with the above arbitrary numerical value as the upper limit or lower limit; the mass fraction of Bi2O3 is preferably 5-15%, more preferably 10-12%, such as 5%, 10%, 15%, preferably a range value with the above arbitrary numerical value as the upper limit or lower limit; the mass fraction of Al2O3 is preferably 10-20%, more preferably 10-15%, such as 10%, 15%, 20%, preferably a range value with the above arbitrary numerical value as the upper limit or lower limit; the mass fraction of B2O3 is preferably 5-15%, more preferably 10-12%, such as 5%, 10%, 15%, preferably a range value with the above arbitrary numerical value as the upper limit or lower limit; the mass fraction of SiO2 is preferably 20-40%, more preferably 25-35%, such as 20%, 25%, 30%, 35%, 40%, preferably a range value with the above arbitrary numerical value as the upper limit or lower limit.

[0061] The above raw materials are weighed in proportion and then ball-milled for mixing. The ball-milling time is preferably 4 to 6 hours, more preferably 5 to 6 hours. The rotation speed of the ball-milling is preferably 150 to 300 rpm, more preferably 200 to 250 rpm.

[0062] The mixed powder after ball milling is melt-treated, which specifically includes the following steps:

[0063] Preheating stage: heating from room temperature to temperature T1, keeping at T1 for 1 to 2 hours, 450℃≤T1≤500℃;

[0064] Heating stage: heating to temperature T2, keeping at T2 for 3 to 5 hours, 500<T2≤1000℃, heating rate is 2~5℃ / min,

[0065] Melting stage: heating to temperature T3, keeping at T3 for 2 to 4 hours, 1000℃<T3≤1300℃;

[0066] Cooling stage: Quickly pour the molten glass into a water tank and control the water temperature at 20-25°C to prevent crystal formation.

[0067] In the present invention, the T1 is preferably 500°C, the T2 is preferably 600-900°C, and the T3 is preferably 1100-1250°C.

[0068] After the glass frit is obtained by melting, the present invention ball-mills the glass frit for 1 to 5 hours, and after the ball-milling, uses a 200-325 mesh screen to sieve the ground material.

[0069] After obtaining the spherical spodumene expansion coefficient adjusting material and the low-temperature glass powder, the present invention mixes the two with polyvinyl pyrrolidone and water in a certain proportion, and stirs them evenly to obtain a uniform slurry.

[0070] In the present invention, the mass ratio of the spherical spodumene expansion coefficient adjusting material to the low-temperature glass powder is preferably 1:(5-20), more preferably 1:(10-15), such as 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, preferably a range value with any of the above values ​​as the upper or lower limit.

[0071] In the slurry, taking the total mass of the slurry as 100%, the total mass fraction of the spherical spodumene expansion coefficient adjusting material and the low-temperature glass powder is 15-38%, more preferably 20-35%; the mass fraction of the polyvinyl pyrrolidone is preferably 2-5%, more preferably 3-4%; the mass fraction of the water is preferably 60-80%, more preferably 70-75%.

[0072] After obtaining the slurry, the present invention sprays the slurry on the surface of the required part of the preheated high-gradient ZnO resistor and performs vitrification to obtain the glass glaze for the high-gradient ZnO resistor.

[0073] In the present invention, the preheating temperature of the high gradient ZnO resistor is preferably 140-160° C., more preferably 150° C., and the preheating time of the high gradient ZnO resistor is preferably 3-5 hours, more preferably 4 hours.

[0074] In the present invention, the pressure of the spray gun during spraying is preferably 0.1-0.3 MPa, more preferably 0.2 MPa; the spraying amount of the slurry is preferably 0.05-0.2 g / cm 3 , more preferably 0.1 to 0.15 g / cm 3 .

[0075] In the present invention, the temperature of the vitrification is preferably 450-550°C, more preferably 500°C, the insulation time of the vitrification is preferably 1-3 hours, more preferably 2 hours, and the heating rate of the vitrification is preferably 1-3°C / min, more preferably 2°C / min; after the vitrification insulation is completed, the temperature is cooled, and the cooling rate is preferably 1-3°C / min, more preferably 2°C / min.

[0076] The present invention also provides a glass glaze for a high-gradient ZnO resistor sheet, which is prepared according to the preparation method described above.

[0077] The present invention also provides an application of the glass glaze for high-gradient ZnO resistor described above in the insulating layer of a high-gradient ZnO resistor. The thermal expansion coefficient of the glass glaze for high-gradient ZnO resistor is controllable and adjustable, and when used as the insulating layer of a high-gradient ZnO resistor, cracks on the glaze surface can be avoided during operation, and the pass rate of the resistor capacity tolerance and the pass rate of the large current impact tolerance can be improved.

[0078] The invention provides a method for preparing glass glaze for high-gradient ZnO resistor sheets, comprising the following steps: A) mixing solid raw materials with sodium polyacrylate and polyvinyl alcohol by ball milling, spray granulating and sintering the obtained mixture in sequence to obtain a spherical spodumene expansion coefficient regulating material; the solid raw materials include 25-35% of aluminum oxide, 45-55% of silicon dioxide and 15-25% of lithium carbonate by mass fraction; the sintering temperature is 950-1100° C., the sintering heat preservation time is 2-4 hours, and the sintering heating rate is 2-5° C. min; B) mixing 30-50% of ZnO, 5-15% of Bi2O3, 10-20% of Al2O3, 5-15% of B2O3 and 20-40% of SiO2 by ball milling, melting and crushing the obtained mixture in sequence to obtain a low-temperature glass powder; the melting The melting treatment is carried out according to the following steps: preheating stage: heating from room temperature to temperature T1, keeping temperature at T1 for 1 to 2 hours, 450°C≤T1≤500°C; heating stage: heating to temperature T2, keeping temperature at T2 for 3 to 5 hours, 500<T2≤1000°C, and heating rate of 2 to 5°C / min; melting stage: heating to temperature T3, keeping temperature at T3 for 2 to 4 hours, 1000°C<T3≤1300°C; cooling stage: quickly pouring the molten glass into a water tank at 20 to 25°C to obtain a glass frit; C) mixing the spherical spodumene expansion coefficient adjusting material, low-temperature glass powder, polyvinyl pyrrolidone and water to obtain a slurry; the mass ratio of the spherical spodumene expansion coefficient adjusting material to the low-temperature glass powder is 1:(5 to 20); D) coating the slurry on the surface of the high-gradient ZnO resistor and vitrifying it to obtain a glass glaze for the high-gradient ZnO resistor. The lead-free low-temperature gradient glass glaze in the present invention not only matches the ZnO resistor, and the resistor has no cracks on the glaze before and after the action, but also meets the insulation requirements of the high-gradient ZnO resistor, further improving the resistance capacity tolerance pass rate and large current impact tolerance pass rate of the resistor.

[0079] In order to further illustrate the present invention, a glass glaze for a high-gradient ZnO resistor, a preparation method thereof and an application thereof provided by the present invention are described in detail below in conjunction with embodiments, but it should not be construed as limiting the protection scope of the present invention.

[0080] Comparative Example 1

[0081] Step 1

[0082] Weigh the following ingredients:

[0083] ZnO: 30%

[0084] Bi2O3: 15%

[0085] Al2O3: 20%

[0086] B2O3: 15%

[0087] SiO2: 20%

[0088] Step 2

[0089] The above ingredients were ball milled for 5 hours at a speed of 200 rpm.

[0090] Step 3

[0091] Preheating stage: room temperature to 500°C, heating rate 5°C / min.

[0092] Heating stage: 500℃ to 1100℃, heating rate is 2℃ / min.

[0093] Insulation melting stage: Insulation at 1100°C for 2 hours.

[0094] Step 4

[0095] Cooling stage: The molten glass is quickly poured into a water tank, and the water temperature is controlled (20-25°C) to prevent crystal formation.

[0096] Step 5

[0097] Grinding: Put the glass frits into the ball mill together and grind for 3 hours. After grinding, use a 200-mesh screen to sieve the ground material.

[0098] Step 6

[0099] The glass glaze slurry is prepared by mixing 28% low-temperature glass powder, 2% PVP, and 70% water, and stirring for 30 minutes to ensure that the PVP is fully dispersed and mixed with the slurry. Stir evenly with a stirring paddle for 60 minutes until a uniform slurry is formed.

[0100] Step 7

[0101] Transfer the above slurry to the material tank, preheat the fired resistor at 150℃ for 4h, and clean the surface of the resistor. Use a spray gun to spray the required part of the resistor, the spray gun pressure is 0.2MPa, and the amount of spray slurry is 0.1g / cm 2 .

[0102] Step 8

[0103] The glass glaze vitrification was heated from room temperature to 500°C at a rate of 2°C / min, and kept at 500°C for 2 hours. The temperature was lowered at a rate of 2°C / min.

[0104] Step 9

[0105] The vitrified resistor is ground, cleaned, dried, aluminum-sprayed, and finally electrically tested.

[0106] After testing, under microscope observation, cracks were found on the side of the resistor. Figure 1 As shown, this embodiment fails to satisfy the expansion coefficient of the resistor and the glass glaze.

[0107] Comparative Example 2

[0108] Step 1

[0109] Alumina (Al2O3): 30%

[0110] Silicon dioxide (SiO2): 50%

[0111] Lithium carbonate (Li2CO3): 20%

[0112] Sodium polyacrylate (0.2% relative to total solid raw materials)

[0113] Polyvinyl alcohol (PVA, 2% relative to the total solid raw materials)

[0114] Step 2

[0115] The above ingredients were fully mixed in a ball mill, stirred for 90 minutes, and then spray granulated at an air pressure of 1-2 bar to obtain a spray granulated material.

[0116] Step 3

[0117] The spray granulated material is placed in a muffle furnace for sintering, the temperature is increased from room temperature to 1100°C, the heating rate is 2°C / min, and the top temperature is kept for 2 hours to obtain spherical spodumene.

[0118] Step 4

[0119] Weigh the following ingredients:

[0120] ZnO: 30%

[0121] Bi2O3: 15%

[0122] Al2O3: 20%

[0123] B2O3: 15%

[0124] SiO2: 20%

[0125] Step 5

[0126] The above ingredients were ball milled for 5 hours at a speed of 200 rpm.

[0127] Step 6

[0128] Preheating stage: room temperature to 500°C, heating rate 5°C / min.

[0129] Heating stage: 500℃ to 1100℃, heating rate is 2℃ / min.

[0130] Insulation stage: Insulation at 1100°C for 2 hours.

[0131] Step 7

[0132] Cooling stage: The molten glass is quickly poured into a water tank, and the water temperature is controlled (20-25°C) to prevent crystal formation.

[0133] Step 8

[0134] Grinding: Put the glass frits into the ball mill together and grind for 3 hours. After grinding, use a 200-mesh screen to sieve the ground material.

[0135] Step 9

[0136] The low-temperature glass glaze slurry is prepared with a mass ratio of spherical spodumene to low-temperature glass powder of (1:3). Subsequently, spherical spodumene and low-temperature glass powder are 28% in total, PVP is 2%, and water is 70%. Continue stirring for 30 minutes to ensure that the PVP is fully dispersed and mixed with the slurry. Stir evenly with a stirring paddle for 60 minutes until a uniform slurry is formed.

[0137] Step 10

[0138] Transfer the above slurry to the material tank, preheat the fired resistor at 150℃ for 4h, and clean the surface of the resistor. Use a spray gun to spray the required part of the resistor, the spray gun pressure is 0.2MPa, and the amount of spray slurry is 0.1g / cm 2 .

[0139] Step 11

[0140] The low temperature glass glaze vitrification is carried out at a temperature rise interval of 2°C / min from room temperature to 500°C, and the temperature is kept at 500°C for 2 hours. The temperature is lowered at 2°C / min.

[0141] Step 12

[0142] The vitrified resistor is ground, cleaned, dried, aluminum-sprayed, and finally electrically tested.

[0143] After testing, under microscope observation, cracks were found on the side of the resistor. Figure 2 As shown, this embodiment fails to meet the requirement of improving the expansion coefficient of the resistor and the glass glaze by adjusting the ratio of spodumene to glass powder.

[0144] Comparative Example 3

[0145] Step 1

[0146] Alumina (Al2O3): 30%

[0147] Silicon dioxide (SiO2): 50%

[0148] Lithium carbonate (Li2CO3): 20%

[0149] Sodium polyacrylate (0.2% relative to total solid raw materials)

[0150] Polyvinyl alcohol (PVA, 2% relative to the total solid raw materials)

[0151] Step 2

[0152] The above ingredients were fully mixed in a ball mill, stirred for 90 minutes, and then spray granulated at an air pressure of 1-2 bar to obtain a spray granulated material.

[0153] Step 3

[0154] The spray granulated material is placed in a muffle furnace for sintering, the temperature is increased from room temperature to 1100°C, the heating rate is 2°C / min, and the top temperature is kept for 2 hours to obtain spherical spodumene.

[0155] Step 4

[0156] Weigh the following ingredients:

[0157] ZnO: 35%

[0158] Bi2O3: 15%

[0159] Al2O3: 15%

[0160] B2O3: 15%

[0161] SiO2: 20%

[0162] Step 5

[0163] The above ingredients were ball milled for 5 hours at a speed of 200 rpm.

[0164] Step 6

[0165] Preheating stage: room temperature to 500°C, heating rate 5°C / min.

[0166] Heating stage: 500℃ to 1100℃, heating rate is 2℃ / min.

[0167] Insulation stage: Insulation at 1100°C for 2 hours.

[0168] Step 7

[0169] Cooling stage: The molten glass is quickly poured into a water tank, and the water temperature is controlled (20-25°C) to prevent crystal formation.

[0170] Step 8

[0171] Grinding: Put the glass frit into the ball mill together. The grinding time is usually 3 hours. After grinding, use a 200-mesh screen to sieve the ground material.

[0172] Step 9

[0173] The low-temperature glass glaze slurry is prepared with a mass ratio of spherical spodumene to low-temperature glass powder of (1:3). Subsequently, spherical spodumene and low-temperature glass powder are added in a total of 28%, PVP 2%, and water 70%. Continue stirring for 30 minutes to ensure that the PVP is fully dispersed and mixed with the slurry. Stir the two evenly with a stirring paddle for 60 minutes until a uniform slurry is formed.

[0174] Step 10

[0175] Transfer the above slurry to the material tank, preheat the fired resistor at 150℃ for 4h, and clean the surface of the resistor. Use a spray gun to spray the required part of the resistor, the spray gun pressure is 0.2MPa, and the amount of spray slurry is 0.1g / cm 2 .

[0176] Step 11

[0177] Low temperature glass glaze vitrification is carried out at a temperature rise interval of 2°C / min from room temperature to 500°C, and then kept at 500°C for 2 hours. The temperature is lowered at 2°C / min.

[0178] Step 12

[0179] The vitrified resistor is ground, cleaned, dried, aluminum-sprayed, and finally electrically tested.

[0180] After testing, under microscope observation, cracks were found on the side of the resistor. Figure 3 As shown, by adjusting the glass glaze formula, the expansion coefficient between it and the zinc oxide resistor could not be improved.

[0181] Example 1

[0182] Step 1

[0183] Alumina (Al2O3): 30%

[0184] Silicon dioxide (SiO2): 50%

[0185] Lithium carbonate (Li2CO2): 20%

[0186] Sodium polyacrylate (0.2% relative to total solid raw materials)

[0187] Polyvinyl alcohol (PVA, 2% relative to the total solid raw materials)

[0188] Step 2

[0189] The above ingredients were fully mixed in a ball mill, stirred for 90 minutes, and then spray granulated at an air pressure of 1-2 bar to obtain a spray granulated material.

[0190] Step 3

[0191] The spray granulated material is placed in a muffle furnace for sintering, the temperature is increased from room temperature to 1100°C, the heating rate is 2°C / min, and the top temperature is kept for 2 hours to obtain spherical spodumene.

[0192] Step 4

[0193] Weigh the following ingredients:

[0194] ZnO: 30%

[0195] Bi2O3: 15%

[0196] Al2O3: 20%

[0197] B2O3: 15%

[0198] SiO2: 20%

[0199] Step 5

[0200] The above ingredients were ball milled for 5 hours at a speed of 200 rpm.

[0201] Step 6

[0202] Preheating stage: room temperature to 500°C, heating rate 5°C / min.

[0203] Heating stage: 500℃ to 1100℃, heating rate is 2℃ / min.

[0204] Insulation stage: Insulation at 1100°C for 2 hours.

[0205] Step 7

[0206] Cooling stage: The molten glass is quickly poured into a water tank, and the water temperature is controlled (20-25°C) to prevent crystal formation.

[0207] Step 8

[0208] Grinding: Put the glass frit into the ball mill together. The grinding time is usually 3 hours. After grinding, use a 200-mesh screen to sieve the ground material.

[0209] Step 9

[0210] The low-temperature glass glaze slurry is prepared with a mass ratio of spherical spodumene to low-temperature glass powder of (1:10). Subsequently, spherical spodumene and low-temperature glass powder are 28% in total, PVP is 2%, and water is 70%. Continue stirring for 30 minutes to ensure that PVP is fully dispersed and mixed with the slurry. Stir the two evenly with a stirring paddle for 60 minutes until a uniform slurry is formed.

[0211] Step 10

[0212] Transfer the above slurry to the material tank, preheat the fired resistor at 150℃ for 4h, and clean the surface of the resistor. Use a spray gun to spray the required part of the resistor, the spray gun pressure is 0.2MPa, and the amount of spray slurry is 0.1g / cm 2 .

[0213] Step 11

[0214] Low temperature glass glaze vitrification is carried out at a temperature rise interval of 2°C / min from room temperature to 500°C, and then kept at 500°C for 2 hours. The temperature is lowered at 2°C / min.

[0215] Step 12

[0216] The vitrified resistor is ground, cleaned, dried, aluminum-sprayed, and finally electrically tested.

[0217] After testing and observation under a microscope, there are no cracks on the side of the resistor. Figure 4 As shown, this indicates that the glass glaze with this formula adjusts the expansion coefficient to match the expansion coefficient of the zinc oxide resistor.

[0218] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing glass glaze for high gradient ZnO resistor, comprising the following steps: A) solid raw material is mixed with sodium polyacrylate and polyvinyl alcohol by ball milling, and the obtained mixed material is spray granulated and sintered in sequence to obtain spherical spodumene expansion coefficient adjusting material; The solid raw material comprises, by mass fraction, 25-35% of aluminum oxide, 45-55% of silicon dioxide and 10-20% of lithium carbonate; The sintering temperature is 950-1100°C, the sintering holding time is 2-4 hours, and the sintering heating rate is 2-5°C min; B) by mass fraction, 30-50% ZnO, 5-15% Bi2O3, 10-20% Al2O3, 5-15% B2O3 and 20-40% SiO2 are ball-milled and mixed, and the obtained mixture is melt-treated and pulverized in sequence to obtain a low-temperature glass powder; The melt processing is carried out according to the following steps: Preheating stage: heating from room temperature to temperature T1, keeping at T1 for 1 to 2 hours, 450℃≤T1≤500℃; Heating stage: heating to temperature T2, keeping at T2 for 3 to 5 hours, 500<T2≤1000℃, heating rate is 2~5℃ / min, Melting stage: heating to temperature T3, keeping at T3 for 2 to 4 hours, 1000℃<T3≤1300℃; Cooling stage: quickly pour the molten glass into a water tank at 20-25°C to obtain a glass frit; C) mixing the spherical spodumene expansion coefficient adjusting material, low-temperature glass powder, polyvinyl pyrrolidone and water to obtain a slurry; The mass ratio of the spherical spodumene expansion coefficient adjusting material to the low-temperature glass powder is 1:(5-20); D) coating the slurry on the surface of a high gradient ZnO resistor and then vitrifying the slurry to obtain a glass glaze for a high gradient ZnO resistor.

2. The preparation method according to claim 1, characterized in that: The mass of the sodium polyacrylate is 0.2-2% of the mass of the solid raw material; The mass of the polyvinyl alcohol is 2-5% of the mass of the solid raw material.

3. The preparation method according to claim 1, characterized in that: The ball milling mixing time in step A) is 60 to 120 minutes; the air pressure of the spray granulation in step A) is 1 to 2 bar.

4. The preparation method according to claim 1, characterized in that: The ball milling mixing time in step B) is 4 to 6 hours, and the rotation speed of the ball milling mixing is 150 to 300 rpm.

5. The preparation method according to claim 1, characterized in that: In the slurry in step C), the total mass fraction of the spherical spodumene expansion coefficient adjusting material and the low-temperature glass powder is 15-38%, the mass fraction of polyvinyl pyrrolidone is 2-5%, and the mass fraction of water is 60-80%.

6. The preparation method according to claim 1, characterized in that: In the step D), the high gradient ZnO resistor is preheated at 140-160° C. for 3-5 hours and then coated with the slurry.

7. The preparation method according to claim 1, characterized in that: The slurry is sprayed on the surface of the high gradient ZnO resistor, the pressure of the spray gun is 0.1-0.3 MPa, and the spraying amount of the slurry is 0.05-0.2 g / cm 3 .

8. The preparation method according to claim 1, characterized in that: The temperature of the vitrification is 450-550° C., the heat preservation time of the vitrification is 1-3 hours, and the heating rate of the vitrification is 1-3° C. / min.

9. A glass glaze for high gradient ZnO resistor, prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the glass glaze for high gradient ZnO resistor as claimed in claim 9 in the insulating layer of a high gradient ZnO resistor.

Citation Information

Cited By

  • Method for selectively depositing vitrification insulating layer on surface of ZnO varistor

    CN121698675A